The Effect of Cash Turnover, Receivables and Inventory on the Liquidity of Manufacturing Companies on the Indonesian Stock Exchange for the 2018-2022 Period - Muhajiroh, Mohamad Ferrari Fariel Noer; Kamila, Nurul (Yayasan Ilomata, 2024)
The company is in a liquid state when the company is able to pay short-term debt. This study aims to determine the manufacturing sector companies listed on Bursa efek Indonesia with the effect of cash turnover, accounts receivable turnover and inventory turnover on liquidity. This research method uses quantitative methods with a sampling model of 5 years of financial statements and a population of manufacturing sector companies listed on Indonesian Stock Exchange. The analysis used is the classic assumption test, the coefficient of determination test, the multiple regression test, the t test and the F test. the results of the analysis show that cash turnover on liquidity is significantly negative, accounts receivable turnover on liquidity is not significant, inventory turnover on liquidity is not significant. While the results of cash turnover, receivables turnover and inventory turnover on liquidity are partially significant. Based on these results, only cash turnover is significant to liquidity, there is an opposite relationship due to negative results. So if cash turnover increases, liquidity decreases and vice versa.